MAPPING SPATIO-TEMPORAL CHANGES IN CLIMATIC SUITABILITY OF CORN IN THE PHILIPPINES UNDER FUTURE CLIMATE CONDITION - Salvacion, Arnold R. (Quaestiones Geographicae, 2017)
This study assessed the spatio-temporal changes in corn climatic suitability in the Philippines under future climate condition. Using extracted climatic data from WorldClim database for the country under baseline and future climate condition, changes in corn suitability was assessed using fuzzy logic approach and published rainfall and temperature requirement of the crop. Based on the data, the large portion of the country will experience increase in monthly total rainfall (88%) while increase in monthly mean and minimum temperature under future climate condition is projected for the entire country. These increases in rainfall and temperature resulted in changes of corn climatic suitability in the country depending on the month and location. On the average, changes in rainfall resulted in reduction (8%) and improvement (6%) in corn suitability while increase in temperature resulted in 5% and 0.4% reduction and improvement, respectively.